Preparatıon and characterızatıon of solıd lıpıd nanopartıcles (slns) for drug delıvery systems - Yargıç, Ayşegül (My University, 2018)
KATI LİPİT NANOPARTİKÜLLERİN İLAÇ TAŞIYICI SİSTEMLER OLARAK HAZIRLANMASI VE KARAKTERİZASYONU İlaç taşıma sistemlerindeki giderek artan teknolojik gelişmeler bu konuya olan ilgiyi artırmıştır. Kontrollü ilaç salımı yapabilen aktif ve pasif ilaç taşıyıcı sistemlerin hazırlanmasında FDA onaylı bileşenlerin kullanılması önemli bir husustur. Bu çalışmada antikanser aktivitesi olan kurkuminin kontrollü salımınını yapabilen katı-lipid çekirdek yapısına sahip ve negatif yüzey yüklü nanopartiküllerden (SLN) oluşan formülasyonlar hazırlanmıştır. Suda çözünürlüğü olmayan kurkumin “nano yapıda ve kendiliğinden oluşan miseller” sayesinde PBS içinde dispers edilmiştir. ilk aşamada ilaç yüklü ve negatif yüzey yüküne sahip kararlı nanomiseller dispersiyon ortamında hazırlanarak karakterize edildi. Nano-miseller zwitter iyonik yapıdaki lesitinin pozitif ucunun katyon değişim reaksiyonu SDS ile etkileşime sokularak elde edilen anyonik amfifilik kompleks (Lesitin-Sodyum Dodesil Sülfat kompleks) yapı emülsiye edilerek hazırlandı. Hazırlanan L-SDS iyonik kompleksin daha kolay emülsiye edilebilmesi ve daha kararlı nano-miseller oluşabilmesi için Tween-80 emülgatör olarak kullanıldı. ikinci aşamada hazırlanan nanomisellere kurkumin yüklenerek ilaç yükleme ve kontrollü salım çalışmaları yapıldı. Kurkuminin PBS içindeki salım profili ultraviyole spektrofotometresi ile zamana karşı incelendi. Hazırlanan kararlı dispersiyonun ortalama partikül büyüklüğü ve dağılımı (Poli Dispersite indeksi) dinamik ışık saçılması ile tayin edildi. Hazırlanan formülasyonlar içinde ilaç yükleme kapasitesi %19, enkapsülasyon verimliliği %39.8, partikül büyüklüğü 302 nm olan kompozisyonun kontrollü kurkumin taşınmasında en uygun kompozisyon olarak seçildi. Bu çalışmada kullanılan bütün kimyasallar FDA onaylı olduğu ve sitotoksik olmadığı için hazırlanan nano-formülasyonların çeşitli hidrofobik antikanser ilaçlarında uygulama potansiyeli yüksektir. Hazırlanan negatif yüklü ve yüksek lipidik özelliğe sahip nano formülasyon literatürde daha önce çalışılmamıştır. Ayrıca curcuminin kontrollü salımının hedeflenmesi açısından da ilk olma özelliğindedir. Anahtar Kelime: Katı-Lipid Nanopartikül (SLN), kurkumin, lesitin, sodyum dodesil sülfat, tween-80, nanomisel, ilaç yükleme, enkapsülasyon verimliliği, antikanser ilaç

PREPARATION AND CHARACTERIZATION OF SOLID LIPID NANOPARTICLES (SLNs) FOR DRUG DELIVERY SYSTEMS Increasing technological developments in the preparation of drug delivery systems have attracting increased interest in this issue. The use of FDA-approved components in the preparation of active and passive drug delivery systems is of important. In this study, nanoparticles having highly lipidic core (SLNP) and negative surface charge have been prepared using FDA approved materials such as lecithin, sodium dodecyl sulphate and tween-80 for curcumin delivery. Because curcumin is insoluble in water, it was dissolved in highly lipidic tails of lecithin and SDS based amphiphilic complex (L-SDS complex). Lecithin is a zwitterionic and amphiphilic natural molecule having two lipidic tails. This molecule is mostly found in animal and plant tissues and has negative and positive charges on both phosphate and tri-methyl ammonium ends, respectively. In order to increase amhiphilicity and thus easy emulsification, the positive end was capped with the negative sulfoxide groups of SDS. Thus, the obtained new amphiphilic complex had one negatively charged head and three long lipidic tails with higher drug loading capacity than lecithin and SDS. First the sterically stable and negatively surface charged nano-micelles were prepared by emulsification of L-SDS complex in the presence of tween-80 as emulgator and their physico-chemical characterization was performed. In the second stage, different formulations was prepared by dissolving of curcumi in lipid tails of L-SDS complex and they were emulsified. Drug loading and release studies of the nano-formulations in micelle form were performed. Release profile of curcumin in PBS was examined against time using UV-VIS spectrophotometer. The average particle size and size distribution of the stable disperse formulation (Poly Dispersity Index) were determined by dynamic light scattering (DLS). Among the prepared formulations, it was accepted that the composition having drug loading capacity 19%, encapsulation efficiency 39.8% and particle size of 302 nm was selected as the most promising composition for the controlled delivery of curcumin. It is notable that, since all of the chemicals used in this study are FDA-approved and non-cyctotoxic, the prepared nano- formulations are expected to have high potential for a variety of hydrophobic anticancer drugs. vii The prepared nano-formulations with negatively surface charge and highly lipid core have not been studied previously in the literature. It is also the first feature to be targeted for the controlled release of curcumin. Key words: Solid-Lipid Nanoparticle (SLN), curcumin, lecithin, sodium dodecyl sulphate, tween-80, nanomicelle, drug loading, encapsulation efficiency, anticancer drug
Keywords: anticancer drug; Anticancer drugs; antikanser ilaç Solid-Lipid Nanoparticle (SLN); Antikanser ilaçlar; Carrier systems; Chemistry, Engineering; Controlled drug release; curcumin; Curcumin - Chemical effect; Drug carrier systems; drug loading; encapsulation efficiency; Encapsulation efficiency in drugs; enkapsülasyon verimliliği; Enkapsülasyon verimliliği, İlaçlarda; İlaç taşıyıcı sistemler; ilaç yükleme; Katı-Lipid nanopartikül (SLN); Kimya, Mühendislik; Kimyasal etkisi; Kontrollü ilaç salımı; Kurkumin; lecithin; lesitin; nanomicelle; nanomisel; sodium dodecyl sulphate; sodyum dodesil sülfat; Solid lipid nanoparticles (SLN); Taşıyıcı sistemler; Tedavide kullanım; tween-80; Use in therapy